2018
DOI: 10.1111/plb.12892
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination and dormancy traits of forbs and shrubs important for restoration of North American dryland ecosystems

Abstract: In degraded dryland systems, native plant community re-establishment following disturbance is almost exclusively carried out using seeds, but these efforts commonly fail. Much of this failure can be attributed to the limited understanding of seed dormancy and germination traits. We undertook a systematic classification of seed dormancy of 26 species of annual and perennial forbs and shrubs that represent key, dominant genera used in restoration of the Great Basin ecosystem in the western United States. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 112 publications
(76 reference statements)
1
35
0
1
Order By: Relevance
“…Restoration practitioners must be able to correctly assign seed dormancy classes because treatments to alleviate seed dormancy are specific to each class (Silveira ; Erickson et al ; Kildisheva et al ; Kildisheva ). Applying the wrong treatment can at best result in failure to break dormancy and at worst kill the seeds.…”
Section: Identification Of Seed Dormancymentioning
confidence: 99%
See 1 more Smart Citation
“…Restoration practitioners must be able to correctly assign seed dormancy classes because treatments to alleviate seed dormancy are specific to each class (Silveira ; Erickson et al ; Kildisheva et al ; Kildisheva ). Applying the wrong treatment can at best result in failure to break dormancy and at worst kill the seeds.…”
Section: Identification Of Seed Dormancymentioning
confidence: 99%
“…Physically dormant seeds will germinate rapidly and to a high extent after scarification. If germination is low even after scarification, this implies poor growth potential of the embryo induced by physiological dormancy; such seeds have combinational (physical + physiological) dormancy (Baskin & Baskin ; Kildisheva et al ).…”
Section: Identification Of Seed Dormancymentioning
confidence: 99%
“…Kildisheva et al . () classified the seed dormancy of 26 key species of the dryland ecosystem of the Great Basin in the USA using a wide temperature range and applying gibberellic acid and karrikinolide, well known dormancy‐breaking compounds. Various dormancy types (physiological, physical, a combination of the two and morphophysiological) were observed and, in all but one species, germination was inhibited below 10 °C.…”
Section: Improving Seed Germinationmentioning
confidence: 99%
“…Interestingly, the addition of GA 3 to the osmo‐priming solution promoted germination in suboptimal conditions (e.g. drought, light/dark) or substituted for the temperature fluctuation requirement of some species, thus expanding the germination “niche” of the tested species to a wider range of environmental conditions (Wagner et al ; Lewandrowski et al ; Kildisheva et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to promote more rapid germination across a wider range of conditions may be particularly salient in regions where environmental conditions are highly stochastic, such as drylands (Pedrero‐López et al ; Erickson et al ; Kildisheva ). Erickson et al () and Kildisheva et al () reported on the potential for the integration of seed priming into the restoration tool kit in the context of mine rehabilitation, either alone or in combination with other seed enhancement techniques. Priming with karrikinolide, a smoke‐derived germination stimulant, was shown to improve germination and emergence of Triodia pungens L. (Erickson et al ; Kildisheva )—a keystone species in the Pilbara bioregion of Western Australia (Nicholas et al ).…”
Section: Introductionmentioning
confidence: 99%